The generation of immune‐induced fever and emotional stress‐induced hyperthermia in mice does not involve brown adipose tissue thermogenesis. Issue 4 (6th March 2020) - Eskilsson, Anna; Shionoya, Kiseko; Enerbäck, Sven; Engblom, David; Blomqvist, Anders
Abstract: We examined the role of brown adipose tissue (BAT) for fever and emotional stress‐induced hyperthermia. Wild‐type and uncoupling protein‐1 (UCP‐1) knockout mice were injected with lipopolysaccharide intraperitoneally or intravenously, or subjected to cage exchange, and body temperature monitored by telemetry. Both genotypes showed similar febrile responses to immune challenge and both displayed hyperthermia to emotional stress. Neither procedure resulted in the activation of BAT, such as the induction of UCP‐1 or peroxisome proliferator‐activated receptor‐γ coactivator‐1α (PGC‐1α) mRNA, or reduced BAT weight and triglyceride content. In contrast, in mice injected with a β3 agonist, UCP‐1 and PGC‐1α were strongly induced, and BAT weight and triglyceride content reduced. Both lipopolysaccharide and the β3 agonist, and emotional stress, induced UCP‐3 mRNA in skeletal muscle. A β3 antagonist did not attenuate lipopolysaccharide‐induced fever, but augmented body temperature decrease and inhibited BAT activation when mice were exposed to cold. An α1 /α2b antagonist or a 5HT1A agonist, which inhibit vasoconstriction, abolished lipopolysaccharide‐induced fever, but had no effect on emotional stress‐induced hyperthermia. These findings demonstrate that in mice, UCP‐1‐mediated BAT thermogenesis does not take part in inflammation‐induced fever, which is dependent on peripheral vasoconstriction, nor in stress‐induced hyperthermia. However, both phenomena may involve UCP‐3‐mediated muscle thermogenesis.